Pengaruh Promosi, Harga dan Kualitas Pelayanan Terhadap Keputusan Pembelian Gathering Planner di PT Showbitz Mitra Utama - Safitri, Silvi Nur; Surbakti, Enda Yunita (Abdimas Indonesian Journal, 2025)
Every company needs to pay attention to promotion, price and service quality factors because these three factors determine the attractiveness of the product in the eyes of consumers and directly influence consumers to make purchasing decisions. This research aims to find out how promotion, price and service quality influence the decision to purchase gathering planners at PT Showbitz Mitra Utama. This research is quantitative descriptive research with the data sources used, namely literature study and distributing questionnaires. The sample in this study was 40 respondents using a saturated sampling technique. The data analysis methods in this research are data quality testing, classical assumption testing, multiple linear regression analysis and hypothesis testing using the SPSS application. The results of the t test in this study show that promotion (X1) partially has a positive and significant effect on purchasing decisions for gathering planners with a t value of 2.618. The t test results show that price (X2) partially has a positive and significant effect on the decision to purchase a gathering planner with a t value of 2.473. The t test results also show that service quality (X3) partially has a positive and significant effect on the decision to purchase a gathering planner with a t value of 3.625. The results of the F test show that promotion (X1), price (X2) and service quality (X3) simultaneously have a positive and significant effect on the decision to purchase a gathering planner with a calculated F value of 24.435. The results of Adjusted R Square (R2) show that promotion (X1), price (X2) and service quality (X3) are able to influence gathering planner purchasing decisions by 64.3% and the remaining 35.7% can be explained by factors not researched. in this research.